1985
DOI: 10.1159/000465766
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IgG Anti-Lewis (a) Antibodies in Cord Sera by Kinetic Elisa

Abstract: Lewis blood group antibodies rarely, if ever, cause hemolytic disease of the newborn. This observation has been attributed to the absence both of Lewis antigens on fetal cells and of maternal IgG Lewis antibody. In the present study, sera from 13 mother-infant pairs were tested for the presence of anti-Lewis (a) by hemagglutination and by a sensitive and specific kinetic enzyme-linked immunosorbent assay. By routine hemagglutination methods, anti-Le^a was present in all maternal samples but absent in all cord … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is generally assumed that most Lewis antibodies are IgM. However, it has been determined that most sera containing Lewis antibodies have an IgG component and that, rarely, some are entirely IgG [135,138,139].…”
Section: Clinical Significance Of Lewis Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally assumed that most Lewis antibodies are IgM. However, it has been determined that most sera containing Lewis antibodies have an IgG component and that, rarely, some are entirely IgG [135,138,139].…”
Section: Clinical Significance Of Lewis Antibodiesmentioning
confidence: 99%
“…In contrast, subjects with the Le(a+b-) phenotype do not have Leb antigens and can make anti-Leb, albeit infrequently [135,[138][139][140]. Most examples of anti-Lea are formed by subjects of the Le(a-b-) ABH secretor phenotype, whereas most examples of anti-Leb are…”
Section: Clinical Significance Of Lewis Antibodiesmentioning
confidence: 99%
“…Nevertheless, Spitalnik et al [7] have demonstrated by means of a sensitive and specific enzymelinked immunosorbent assay that an IgG component occurred in all 13 maternal sera studied which were anti-Leacarriers, and that in 12 of the cases the antibody having crossed the placenta could be detected in cord serum samples. On the other hand, Longworth et al [8], using potent mouse monoclonal antiLewis grouping reagents, reported that 8% of cord blood samples reacted weakly with monoclonal, but not with polyclonal, antiLe".…”
mentioning
confidence: 99%